Conductive member, its manufacturing method, process cartridge and electrophotographic image forming apparatus
The conductive member with a matrix-domain structure and controlled resistivity addresses discharge stability issues in high-speed electrophotographic image forming, ensuring stable and high-quality image output by leveling potential unevenness.
Patent Information
- Application Number
- JP2020174639
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-18
- Filing Date
- 2020-10-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing conductive members in electrophotographic image forming apparatuses, such as charging members, experience insufficient discharge stability during high-speed image forming processes, leading to ghost images due to unlevelled potential unevenness on the surface of charged objects.
A conductive member with a conductive layer composed of a matrix containing a crosslinked product of first and second rubbers and dispersed domains, featuring a matrix-domain structure with exposed domains at recesses, and specific resistivity ranges to ensure stable discharge and charge accumulation.
The conductive member stabilizes discharge and uniformly charges the electrophotographic photoreceptor, preventing ghost images and enabling high-quality image formation even at high speeds.
Smart Images

Figure 0007612372000014 
Figure 0007612372000015 
Figure 0007612372000016
Abstract
Description
[Technical field]
[0001] The present disclosure is directed to an electrophotographic conductive member used as a charging member, a developing member or a transfer member in an electrophotographic image forming apparatus, a process cartridge, and an electrophotographic image forming apparatus. [Background technology]
[0002] An electrophotographic image forming apparatus (hereinafter also referred to as "electrophotographic apparatus") uses conductive members such as a charging member, a transfer member, and a developing member. Known conductive members include a conductive support and a conductive layer provided on the support. The conductive member transports electric charge from the conductive support to the conductive member surface and provides electric charge to a contacting object by discharge or frictional charging.
[0003] The charging member is a member that generates a discharge between itself and an electrophotographic photoreceptor (hereinafter also referred to as "photoreceptor"), thereby charging the surface of the photoreceptor. The developing member is a member that controls the charge of the developer coated on its surface by frictional charging, gives a uniform charge distribution, and then uniformly transfers the developer to the surface of the electrophotographic photoreceptor according to the applied electric field. The transfer member is a member that transfers the developer from the electrophotographic photoreceptor to a print medium or an intermediate transfer body, and at the same time generates a discharge to stabilize the developer after transfer.
[0004] These conductive members are required to achieve uniform charging of the objects they come into contact with, such as electrophotographic photosensitive members, intermediate transfer bodies, and print media, and roller-shaped conductive members are preferably used.
[0005] As a charging member for contact charging, Patent Document 1 discloses a rubber composition having an island structure including a polymer continuous phase made of an ionically conductive rubber material and a polymer particle phase made of an electronically conductive rubber material, and the ionically conductive rubber material has a volume resistivity of 1×10 12The document discloses an electrostatically-charged member that is mainly composed of raw rubber A having a resistance of Ω·cm or less, and that is characterized in that the electronically-conductive rubber material is made conductive by blending conductive particles into raw rubber B. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-3651 A Summary of the Invention [Problem to be solved by the invention]
[0007] According to the study by the present inventors, although the charging member according to Patent Document 1 has a uniform and stable electric resistance value, in the recent high-speed image formation process, the discharge stability may not be sufficient. Specifically, when the charging member according to Patent Document 1 is used for forming an electrophotographic image, the minute potential unevenness formed on the surface of the charged body before the charging process cannot be sufficiently leveled, and an electrophotographic image (hereinafter also referred to as a "ghost image") may be formed in which an image that should not be formed due to the potential unevenness appears superimposed on the original image.
[0008] One aspect of the present disclosure is directed to providing a conductive member capable of stably forming high-quality images even when applied to a high-speed electrophotographic image forming process. Conductivity The present invention is directed to providing a method for manufacturing a member, and a process cartridge and an electrophotographic image forming apparatus which contribute to the formation of high-quality electrophotographic images. [Means for solving the problem]
[0009] According to one aspect of the present disclosure, A conductive member having a conductive support and a conductive layer, The conductive layer is a single layer. Conductivity A surface layer of the component, the conductive layer has a matrix containing a cross-linked product of a first rubber and a plurality of domains dispersed in the matrix, Each of the domains includes a crosslinked product of a second rubber and conductive particles, The conductive member outside the surface has a plurality of recesses; At least a portion of the surface of the domain is exposed to the outer surface of the conductive member at the bottom of the recess; The volume resistivity of the matrix rate is 1.0 × 10 12 Larger than Ωcm The volume resistivity of the conductive layer is 1.0×10 5 Ωcm or more 1.0×10 8 Ωcm or less, The conductive support and the conductive member Other The current value when a DC voltage of 80 V is applied between the cantilever of an atomic force microscope in contact with the surface of the matrix constituting the surface and the cantilever is defined as A1. The conductive support and the conductive member Other When a direct current voltage of 80 V is applied between the cantilever of an atomic force microscope in contact with the surface of the domain constituting the surface and the current value A2, a conductive member is provided in which A2 is 20 times or more larger than A1.
[0010] According to another aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including an electrophotographic photoreceptor and a charging member arranged so as to be able to charge the electrophotographic photoreceptor, the charging member being the above-described conductive member.
[0011] According to another aspect of the present disclosure, there is provided a process cartridge for electrophotography that is configured to be detachably mountable to a main body of an electrophotographic image forming apparatus and that includes the above-mentioned conductive member.
[0012] According to still another aspect of the present disclosure, there is provided a method for producing the above-mentioned conductive member, comprising the steps of: The following steps (A) to (D): (A) preparing a domain-forming rubber composition comprising the conductive particles and the second rubber; (B) preparing a rubber composition for forming a matrix containing the first rubber; (C) kneading the domain-forming rubber composition with the matrix-forming rubber composition to prepare a rubber composition having a matrix-domain structure; and (D) extruding the rubber composition having a matrix-domain structure from a crosshead together with a conductive support to cover the periphery of the conductive support with the rubber composition having a matrix-domain structure; Have The method for producing a conductive member is provided in which, when the die swell value of the rubber composition for forming a domain is DS(d) and the die swell value of the rubber composition for forming a matrix is DS(m), the die swell value ratio DS(m) / DS(d) is greater than 1.0. Effect of the Invention
[0013] According to one aspect of the present disclosure, it is possible to provide a conductive member capable of stably providing high-quality images without generating ghost images even when applied to a high-speed electrophotographic image forming process. According to another aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus capable of forming high-quality electrophotographic images. [Brief description of the drawings]
[0014] [Figure 1A] Schematic diagram of electrophotographic process to explain surface potential unevenness [Figure 1B] Surface potential profile of a photosensitive drum for explaining surface potential unevenness [Diagram 2] Schematic diagram showing a rubber composition having a matrix-domain structure [Figure 3A] Schematic diagram of the matrix-domain structure on the outer surface of a conductive member [Figure 3B] Schematic diagram of the matrix-domain structure on the outer surface of a conductive member [Figure 4A] Illustration of the discharge area [Figure 4B] Illustration of the discharge area [Diagram 5] FIG. 1 is a diagram showing a schematic configuration of a crosshead extrusion device. [Figure 6] FIG. 1 illustrates a configuration of an electrophotographic image forming apparatus. [Figure 7] FIG. 2 illustrates a configuration of a process cartridge. [Figure 8] FIG. 1 is a diagram showing the schematic configuration of a device for measuring the current of a charging roller using an AFM. [Figure 9] FIG. 1 shows an example of a measurement result of the depth of a recess by AFM. [Figure 10] FIG. 1 is a diagram showing a schematic configuration of a discharge light observation device. [Figure 11A] Schematic diagram showing a discharge light image and a contact area [Figure 11B] Schematic diagram showing a discharge light image and a contact area [Figure 12] An example of a current profile measurement result using an AFM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] According to the investigations of the present inventors, the charging member according to Patent Document 1 sometimes caused the above-mentioned ghost image to occur when evaluated in the main body at the above-mentioned high speed. We speculate that the mechanism by which ghost images occur is as follows. The phenomenon of the occurrence of ghost images is explained with reference to FIG. 1. FIG. 1A shows a schematic diagram of an electrophotographic process, in which a charging member 11 for charging an electrophotographic photosensitive member (hereinafter also referred to as a "photosensitive drum") 12 is arranged in contact with the electrophotographic photosensitive member 12. An arrow 13 indicates a measurement position of the surface potential of the photosensitive drum before charging, and an arrow 14 indicates a measurement position of the surface potential of the photosensitive drum after charging. (b) of FIG. 1B shows a change (potential profile) in the surface potential of the photosensitive drum at the measurement position 13, and (c) and (d) of FIG. 1B show a change (potential profile) in the surface potential of the photosensitive drum at the measurement position 14. In the graph of FIG. 1B, the vertical axis indicates the surface potential (SP), and the horizontal axis indicates the measurement position (P). In (c) and (d) of FIG. 1B, the dashed lines indicate the potential profile before charging shown in (b) of FIG. 1B. Normally, after the transfer process, the photosensitive drum 12 before charging in the next image forming process has potential unevenness resulting from the electrostatic latent image formed in the previous image forming process. If such potential unevenness cannot be made uniform in the next charging process, the potential unevenness as shown by the solid line in (c) of FIG. 1B remains, causing a ghost (G) image to occur. Therefore, in the next charging process, it is important to sufficiently uniform the potential unevenness on the surface of the photosensitive drum in order to prevent the occurrence of a ghost image.
[0016] However, the charging member disclosed in Patent Document 1 is considered to have an insufficient ability to impart charge to a photosensitive drum in a high-speed process.
[0017] On the other hand, with the conductive member according to the present disclosure, the surface potential of the photosensitive drum having potential unevenness as shown in FIG. 1B(b) can be made uniform as shown by the solid line in FIG. 1B(d).
[0018] The conductive member according to the present disclosure will be described. The conductive member has a conductive support and a conductive layer. The conductive layer is a surface layer composed of a single layer, and has a matrix containing a cross-linked product of a first rubber and a plurality of domains dispersed in the matrix, each of which contains a cross-linked product of a second rubber and conductive particles. In order to form a matrix-domain structure (also called a sea-island structure), it is preferable that the first rubber and the second rubber are different materials. The outer surface of the conductive member has a plurality of recesses, and the surfaces of at least some of the domains are exposed to the outer surface of the conductive member at the bottoms of the recesses. The volume resistivity of the matrix is 1.0×10 12 Ωcm, and the volume resistivity of the conductive layer is 1.0×10 5 Ωcm or more 1.0×10 8 It is less than Ωcm. Here, the current value when a DC voltage of 80 V is applied between the conductive support of the conductive member and the cantilever of an atomic force microscope in contact with the surface of the matrix constituting the surface of the conductive member is defined as A1. Also, the current value when a DC voltage of 80 V is applied between the conductive support and the cantilever of an atomic force microscope in contact with the surface of the domain constituting the surface of the conductive member is defined as A2. A2 is 20 times or more larger than A1.
[0019] In the conductive member according to this embodiment, domains constituted of the second cross-linked rubber and conductive particles are dispersed in a matrix made of the first cross-linked rubber, and the volume resistivity of the matrix is 1.0×10 12 Greater than Ωcm.
[0020] The present inventors surmise that the reason why the conductive member having the above-mentioned configuration can smooth out the potential unevenness as shown in FIG. 1B(b) as shown in FIG. 1B(d) is as follows. That is, the so-called contact charging utilizes discharge that occurs from the surface of the charging member toward the surface of the photosensitive drum in a discharge area where the relationship between the strength of the electric field and the distance of the gap in the vicinity of the contact part between the charging member and the photosensitive drum satisfies Paschen's law. Here, in the downstream area of the discharge area closer to the contact part, the difference in surface potential between the charging member and the photosensitive drum becomes smaller, so that discharge from the charging member is less likely to occur. In particular, when the amount of charge discharged in one discharge is large, it is considered that the surface potential of the photosensitive drum after the charging process is substantially dominated by discharge in the upstream area 43b-1 of the discharge area 43b shown in FIG. 4B, which is far from the contact part (N). In addition, in FIGS. 4A and 4B, 41 is a photosensitive drum, and 42 is a conductive member as a charging member. On the other hand, the conductive member according to the present disclosure can reduce the amount of charge discharged in one discharge for the reasons described below. Therefore, the potential difference between the charging member and the photosensitive drum is maintained to some extent even downstream of the discharge area. In addition, since the domain that serves as the discharge point is present at the bottom of the recess, a gap can be secured between the discharge point and the photosensitive drum surface even at a position closer to the contact portion, and discharge to the photosensitive drum can be continued even at a position immediately adjacent to the contact portion. As a result, as shown in FIG. 4A, the discharge area 43a can be expanded, and it is considered that the total amount of charge given to the photosensitive drum can be increased.
[0021] The reason why minute discharges are possible with the conductive member according to the present disclosure will be explained below. It is believed that when a charging bias is applied between the support of the conductive member and the electrophotographic photoreceptor, electric charges move from the support side of the conductive layer to the opposite side, i.e., the outer surface side of the conductive member, in the conductive layer as follows: That is, electric charges are accumulated in the vicinity of the interface between the matrix and the domain. The charge is then transferred in sequence from the domain located on the conductive support side to the domain located on the opposite side to the conductive support side, and reaches the surface of the conductive layer opposite to the conductive support side (hereinafter also referred to as the "outer surface of the conductive layer"). At this time, if the charges of all the domains move to the outer surface side of the conductive layer in one charging step, it will take time to accumulate the charges in the conductive layer in preparation for the next charging step. This makes it difficult to achieve stable discharge in a high-speed electrophotographic image forming process. Therefore, even when a charging bias is applied, it is preferable to prevent simultaneous transfer of charges between domains. In addition, since the movement of charges is restricted in a high-speed electrophotographic image forming process, it is preferable to accumulate a sufficient amount of charges in each domain in order to discharge a sufficient amount of charges in one discharge.
[0022] The conductive layer has a matrix and a plurality of domains dispersed in the matrix. The matrix contains a first rubber, and the domains contain a second rubber and an electronic conductive agent. The matrix and the domains satisfy the following components (i) and (ii). Component (i): The volume resistivity of the matrix is 1.0×10 12 Greater than Ω·cm. Component (ii): The volume resistivity of the domain is smaller than the volume resistivity of the matrix.
[0023] A conductive member having a conductive layer that satisfies the components (i) and (ii) can accumulate sufficient charge in each domain when a bias is applied between the conductive member and the photoconductor. In addition, because the domains are separated by a matrix with a high volume resistivity, simultaneous transfer of charge between the domains can be suppressed. This makes it possible to prevent most of the charge accumulated in the conductive layer from being released in a single discharge. As a result, even immediately after one discharge is completed, the conductive layer can still have charges stored therein for the next discharge. Therefore, it is possible to stably generate discharges in a short cycle. Such discharges achieved by the conductive member according to the present disclosure are hereinafter also referred to as "fine discharges."
[0024] As described above, a conductive layer having a matrix-domain structure that satisfies the components (i) and (ii) can suppress the occurrence of simultaneous charge transfer between domains when a bias is applied, and can accumulate sufficient charge within the domains. Therefore, the conductive member can continuously and stably apply charge to a member to be charged even when applied to an electrophotographic image forming apparatus with a high process speed.
[0025] The two effects of the increased discharge width near the nip and the micro-discharge described above make it possible to smooth out the uneven surface potential before the charging process begins by means of a precise and stable discharge during charging, thereby making it possible to suppress the aforementioned ghost images even in high-speed processes.
[0026] <Conductive materials> 2 is a cross-sectional view perpendicular to the longitudinal direction of a conductive roller 11 according to one embodiment of the present disclosure. The conductive roller 11 has a cylindrical or hollow cylindrical conductive support 15 and a conductive layer 16 formed on the outer circumferential surface of the support. Fig. 3A shows a cross-sectional view of the conductive layer in a direction perpendicular to the longitudinal direction of the conductive roller, and Fig. 3B shows a perspective view of the surface side of the conductive layer. The conductive layer has a structure having a matrix 21 and domains 22 (hereinafter, also referred to as a "matrix-domain structure"). The domains 22 contain conductive particles.
[0027] <Conductive support> The conductive support may be appropriately selected from those known in the field of electrophotographic conductive members. Examples include metals or alloys such as aluminum, stainless steel, conductive synthetic resins, iron, and copper alloys. Furthermore, these may be subjected to oxidation treatment or plating treatment with chromium, nickel, etc. As the plating method, either electric plating or electroless plating may be used, but electroless plating is preferred from the viewpoint of dimensional stability. Examples of the electroless plating used here include nickel plating, copper plating, gold plating, and various other alloy platings. The plating thickness is preferably 0.05 μm or more, and considering the balance between work efficiency and rust prevention ability, the plating thickness is preferably 0.1 to 30 μm. Examples of the shape of the conductive support include a cylindrical shape or a hollow cylindrical shape. The outer diameter of this conductive support is preferably in the range of φ3 mm to φ10 mm.
[0028] <Conductive layer> <Matrix> The matrix contains a crosslinked product of the first rubber, and the volume resistivity ρm of the matrix is 1.0×10 12 Ωcm or greater than 1.0×10 17 The volume resistivity of the matrix is preferably 1.0×10 12By making the resistance larger than Ωcm, as mentioned above, the electric charge moving in the conductive layer moves to the surface of the conductive material while repeating movement and stopping. Therefore, even if a bias is applied, the transfer of electric charge between domains can be prevented at the same time, and a precise and stable discharge can be performed. In addition, the volume resistivity ρm is 1.0×10 17 By setting the resistivity to Ωcm or less, it is possible to smoothly discharge from the conductive member to the member to be charged when a charging bias is applied between the conductive support and the member to be charged. The method for measuring the volume resistivity of the matrix will be described later.
[0029] <First Rubber> The first rubber is the most mixed in the rubber composition for forming the conductive layer. Since the crosslinked product of the rubber governs the mechanical strength of the conductive layer, the first rubber used is one that exhibits the strength required for the conductive member for electrophotography after crosslinking in the conductive layer. In addition, the volume resistivity of the matrix is set to the above-mentioned 1.0×10 12 Considering that the resistivity should be larger than Ωcm, the first rubber is preferably as follows. Natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), butyl rubber (IIR), ethylene-propylene rubber (EPM), ethylene-propylene-diene terpolymer rubber (EPDM), chloroprene rubber (CR), and silicone rubber.
[0030] <Reinforcing agent> The matrix can contain a reinforcing agent to the extent that it does not affect the conductivity of the matrix. An example of the reinforcing agent is reinforcing carbon black with low conductivity. Specific examples of reinforcing carbon black include FEF, GPF, SRF, and MT carbon. Furthermore, to the first rubber forming the matrix, fillers, processing aids, vulcanization aids, vulcanization accelerators, vulcanization acceleration aids, vulcanization retarders, antioxidants, softeners, dispersants, colorants, and the like, which are generally used as compounding agents for rubber, may be added as necessary.
[0031] <domain> The domain includes a crosslinked product of the second rubber and conductive particles. Here, the conductive property is defined as a volume resistivity of 1.0×10 8 It is defined as less than Ωcm.
[0032] <Second Rubber> Specific examples of rubbers that can be used as the second rubber are given below. NR, IR, BR, SBR, IIR, EPM, EPDM, CR, NBR, H-NBR, silicone rubber, urethane rubber (U).
[0033] <Conductive particles> Examples of conductive particles include carbon materials such as conductive carbon black and graphite; conductive oxides such as titanium oxide and tin oxide; metals such as Cu and Ag; and electron conductive agents such as particles coated with conductive oxides or metals. Two or more of these conductive particles may be mixed in appropriate amounts and used. It is preferable to use conductive carbon black as the conductive particles. Specific examples of conductive carbon black include gas furnace black, oil furnace black, thermal black, lamp black, acetylene black, and ketjen black.
[0034] <Domain diameter> The arithmetic mean value of the equivalent circle diameter of the domains (hereinafter, simply referred to as "domain diameter") is preferably 0.10 μm or more and 5.00 μm or less. By setting the average domain diameter to 0.10 μm or more, the path along which charges move can be more effectively restricted in the conductive layer, more preferably 0.15 μm or more, and even more preferably 0.20 μm or more. Moreover, by making the average value of the domain diameter 5.00 μm or less, the ratio of the surface area to the total volume of the domain, i.e., the specific surface area, can be exponentially increased, and the efficiency of discharging electric charges from the domain can be dramatically improved. For the above reasons, the average value of the domain diameter is preferably made 2.00 μm or less, and more preferably 1.00 μm or less. The method of calculating the domain diameter will be described later.
[0035] <Distance between adjacent domains (hereinafter also referred to as "inter-domain distance")> The arithmetic mean value of the interdomain distance is preferably 0.2 μm or more and 4.0 μm or less. In order for the conductive layer in which the domains are dispersed in the matrix to carry and discharge sufficient electric charge to the outer surface of the conductive member, the interdomain distance is preferably 4.0 μm or less, particularly 3.0 μm or less. On the other hand, in order to reliably separate the domains from each other with the matrix, which is an insulating region, and to accumulate sufficient electric charge in the domains, the interdomain distance is preferably 0.2 μm or more, particularly 0.3 μm or more. The method of calculating the interdomain distance will be described later.
[0036] <Method of manufacturing conductive member> The conductive member having the conductive layer according to this embodiment can be formed, for example, by a method including the following steps (A) to (D). Step (A): A step of preparing a domain-forming rubber composition (hereinafter also referred to as "CMB") containing carbon black and a second rubber. Step (B): A step of preparing a matrix-forming rubber composition (hereinafter also referred to as "MRC") containing a first rubber. Step (C): A step of kneading the CMB and the MRC to prepare a rubber composition having a matrix-domain structure. Step (D): A step of extruding the rubber composition having a matrix-domain structure from a crosshead together with a conductive support (core metal) to coat the periphery of the core metal with the rubber composition having a matrix-domain structure.
[0037] 5 is a schematic diagram of a crosshead extrusion molding machine 50. The crosshead extrusion molding machine 50 is a device for evenly coating an unvulcanized rubber composition 52 around a core metal 51, thereby producing an unvulcanized rubber roller 53 having the core metal 51 at its center.
[0038] The crosshead extrusion molding machine 50 is provided with a crosshead 54 into which a core bar 51 and an unvulcanized rubber composition 52 are fed, a conveying roller 55 that feeds the core bar 51 to the crosshead 54, and a cylinder 56 that feeds the unvulcanized rubber composition 52 to the crosshead 54. The conveying rollers 55 continuously feed the multiple cores 51 in the axial direction to the crosshead 54. The cylinder 56 has a screw 57 therein, and the unvulcanized rubber composition 52 is fed into the crosshead 54 by the rotation of the screw 57. When the core metal 51 is fed into the crosshead 54, the entire circumference thereof is covered with the unvulcanized rubber composition 52 fed into the crosshead from the cylinder 56. Then, the core metal 51 is sent out from the die 58 at the exit of the crosshead 54 as an unvulcanized rubber roller 53 having a surface covered with the unvulcanized rubber composition 52.
[0039] Here, when the die swell value of the CMB prepared in step (A) is DS(d) and the die swell value of the MRC prepared in step (B) is DS(m), DS(m) / DS(d) is made larger than 1.00, thereby making it possible to form the conductive member according to this embodiment. The die swell value will be described. When a rubber composition is extruded using a die extruder, the rubber composition compressed by the application of pressure in the extruder is extruded from the extrusion port, and the pressure is released, causing the extruded rubber composition to expand, and its thickness becomes thicker than the size of the gap at the extrusion port of the die. The die swell value is an index that indicates the degree of expansion of the rubber composition when extruded from the extrusion port. In the method for producing an electrostatically charged member according to the present embodiment, a rubber composition having a matrix-domain structure is prepared by mixing CMB for domain formation and MRC for matrix formation, which satisfy the relationship DS(m) / DS(d)>1.00. Then, the rubber composition having the matrix-domain structure is extruded from the extrusion port of the crosshead. Then, since the expansion rate of the matrix is greater than the expansion rate of the domain, the matrix around the domain present on the surface of the extruded rubber composition rises, and as a result, a layer of an unvulcanized rubber composition having a recess on the surface and a domain at the bottom of the recess is formed. In order to more easily form the configuration of the conductive layer according to the present embodiment, the DS(m) / DS(d) is preferably 1.15 or more. By making it 1.15 or more, a recess in which the domain is exposed can be more effectively formed. The die swell value of the CMB for domain formation and the MRC for matrix formation can be adjusted, for example, by the type and amount of filler added. Specifically, the die swell value decreases as the amount of filler added increases. In addition, when fillers with high rubber reinforcing effect such as carbon black and silica, or scaly fillers such as bentonite and graphite are used as fillers, the die swell value decreases compared to when calcium carbonate is used. The conductive particles added to the CMB are also considered to be this type of filler.
[0040] In the step (C), examples of a method for kneading the CMB that forms the domains and the MRC that forms the matrix to obtain an unvulcanized rubber composition having a matrix-domain structure include the methods described in the following (i) and (ii). (i) A method in which the CMB that will become the domains and the MRC that will become the matrix are mixed using a closed type mixer such as a Banbury mixer or a pressure kneader, and then the CMB that will become the domains, the MRC that will become the matrix, and raw materials such as vulcanizing agents and vulcanization accelerators are kneaded together using an open type mixer such as an open roll. (ii) A method in which the CMB that will become the domains is mixed using an internal mixer such as a Banbury mixer or a pressure kneader, and then the raw materials for the CMB that will become the domains and the MRC that will become the matrix are mixed in an internal mixer, and then raw materials such as vulcanizing agents and vulcanization accelerators are kneaded and integrated using an open mixer such as an open roll.
[0041] The unvulcanized rubber roller formed in the step (D) can then be subjected to a vulcanization step (E) to produce the conductive member according to this embodiment. Specific examples of the heating method include hot air oven heating in a gear oven, heat vulcanization using far infrared rays, and steam heating in a vulcanizer. Among these, hot air oven heating and far infrared heating are preferred because they are suitable for continuous production.
[0042] In order to better maintain the surface shape formed by the above method, in which the domain exists at the bottom of the recess, it is preferable not to polish the surface of the obtained conductive member (conductive roller). Therefore, when the outer shape of the conductive layer of the conductive member according to this embodiment is made into a crown shape, it is preferable to form the outer diameter shape of the unvulcanized rubber layer into a crown shape by controlling the extrusion speed of the core metal from the crosshead and the extrusion speed of the unvulcanized rubber composition. The crown shape refers to a shape in which the outer diameter of the central part in the longitudinal direction of the core metal of the conductive layer is larger than the outer diameter of the end part.
[0043] Specifically, the extruder shown in FIG. 50 The relative ratio between the core metal feeding speed by the conveying roller 55 of the core metal 51 and the feeding speed of the unvulcanized rubber composition from the cylinder 56 is changed. At this time, the feeding speed of the unvulcanized rubber composition 52 from the cylinder 56 to the crosshead 54 is kept constant. The thickness of the unvulcanized rubber composition 52 is determined by the ratio between the feeding speed of the core metal 51 and the feeding speed of the unvulcanized rubber composition 52. This makes it possible to form the conductive layer into a crown shape without polishing. The vulcanized rubber composition on both ends of the vulcanized rubber roller is removed in a separate process later, completing the vulcanized rubber roller. Therefore, both ends of the core metal of the completed vulcanized rubber roller are exposed. The conductive layer on the surface may be subjected to a surface treatment by irradiation with ultraviolet light or electron beams.
[0044] <Matrix-Domain Structure> The conductive member formed through the method including the above steps (A) to (D) has a matrix-domain structure. The observation method of the matrix-domain structure will be described later, but the number of domains dispersed in the matrix in a cube with a side length of 10 μm is preferably 500 or less. If the number of domains is more than 500, the distance between the domains becomes short, so that the accumulation of charge at the interface between the domain and the matrix becomes insufficient, and the denseness of discharge may be impaired. In the matrix-domain structure on the outer surface, the domains 22 are exposed at the recesses 32 as shown in FIGS. 3A and 3B. In order to effectively expand the discharge width toward the nip vicinity side at the upstream part of the nip, the ratio of the domains 22 exposed to the outer surface at the bottom of the recesses 32 (hereinafter referred to as the "domain exposure rate at the recesses") is preferably 50% or more. In addition, the depth of the domains exposed at the recesses from the outer surface of the matrix is preferably 2 μm or more. In this embodiment, the domains are defined as being exposed to the outer surface when the current value is measured by AFM as described later, and the current value is smaller by one order of magnitude or more than the average current value of the matrix part, as shown by 121 in FIG. 12. In addition, the exposed domains are defined as being recessed when the height is smaller by 1.0 μm or more than the average height of the matrix in the height measurement by AFM as described later. In order to cause the above-mentioned micro-discharge, it is necessary to discharge only from the domain. In the present disclosure, when a DC voltage of 80 V is applied between the conductive support and the cantilever of an atomic force microscope in contact with the surface of the matrix constituting the surface of the conductive member, the current value is A1, and when a DC voltage of 80 V is applied between the conductive support and the cantilever of an atomic force microscope in contact with the surface of the domain constituting the surface of the conductive member, the current value is A2, A2 is 20 times or more than A1.
[0045] (Electrophotographic image forming apparatus) The charging member according to one embodiment of the present disclosure can be used in an electrophotographic image forming apparatus such as a laser printer, and in a process cartridge that is detachably mountable to the electrophotographic image forming apparatus. 6 shows a schematic cross-sectional view of an electrophotographic image forming apparatus according to one embodiment of the present disclosure. An electrophotographic photoreceptor (hereinafter, referred to as "photoreceptor") 61 as a member to be charged is made up of a conductive support and a photosensitive layer formed on the conductive support, and has a cylindrical shape. It is driven at a predetermined peripheral speed in a clockwise direction on the drawing around the axis. The charging roller 62 is placed in contact with the photoreceptor 61 and charges the photoreceptor 61 to a predetermined potential. The charging roller 62 is made of a core and a conductive layer formed on the core, and both ends of the core are pressed against the photoreceptor 61 by pressing means (not shown), and is rotated in response to the driving of the photoreceptor 61. A predetermined DC voltage is applied to the core by a rubbing electrode of a power source 63, so that the photoreceptor 61 is charged to a predetermined potential. The charged photoreceptor 61 is then exposed to light by an exposure device 64 to form an electrostatic latent image corresponding to the desired image information on its circumferential surface. The electrostatic latent image is then visualized as a toner image by a developing device 65. The toner images are transferred to a transfer material P in sequence. The transfer material P is conveyed from the paper feed device to a transfer section between the photoreceptor 61 and a transfer device 66 at an appropriate timing in synchronization with the rotation of the photoreceptor 61. The transfer device 66 is a transfer roller, which charges the back of the transfer material with a polarity opposite to that of the toner, thereby transferring the toner image on the photoreceptor 61 side to the transfer material. The transfer material with the toner image transferred to its surface is separated from the photoreceptor 61 and conveyed to a fixing device 67, where the toner is fixed, and the material is output as an image formation product. After the image transfer, the peripheral surface of the photoreceptor 61 is cleaned by a cleaning device 68, typically an elastic blade, to remove toner and other residues remaining on the surface of the photoreceptor 61. The cleaned peripheral surface of the photoreceptor 61 is moved to the next cycle of the electrophotographic image formation process.
[0046] <Process cartridge> A process cartridge according to one embodiment of the present disclosure is shown in Fig. 7. The process cartridge is detachably mountable to an electrophotographic image forming apparatus. The process cartridge includes an electrophotographic photosensitive member 71, a charging roller 74 arranged so as to be able to charge the electrophotographic photosensitive member 71, a developing roller 72, and a cleaning member 73. The charging member according to one embodiment of the present disclosure is used as the charging roller 74. EXAMPLES
[0047] Example 1 <1-1. Preparation of domain forming rubber mixture (CMB)> The carbon master batch (CMB) raw materials shown in Table 1 below were mixed in the amounts shown in Table 1 to prepare CMB1. The mixer used was a 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes.
[0048] [Table 1]
[0049] <1-2. Calculation of CMB die swell> For the CMB1 prepared above, the die swell value (DS(d)) was calculated by the following method. That is, the die swell is measured using a capillary rheometer (product name: Capillograph 1D type, manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS K 7199:1999. The measurements were performed under the following conditions: capillary length: 10 mm, capillary diameter D: 2 mm, furnace diameter: 9.55 mm, load cell type: 20 kN, and measurement temperature: 80° C. The die swell was measured at a piston speed of 100 mm / min (shear rate: 1.52×10 2 ) The diameter R [mm] of the extruded strand was measured, and the die swell was calculated as DS = R / D.
[0050] <1-3. Preparation of matrix forming rubber mixture (MRC)> A matrix-forming rubber mixture (MRC) was obtained by mixing the materials of the types and amounts shown in Table 2 in a pressure kneader. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes. For the obtained mixture, the die swell value (DS(m)) of the mixture was calculated in the same manner as in the calculation method of the die swell of CMB.
[0051] [Table 2]
[0052] <1-4. Preparation of conductive rubber composition 1> The types and amounts of each material shown in Table 3 were mixed in an open roll to prepare a rubber composition for molding a conductive member. An open roll with a roll diameter of 12 inches was used as the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.5 mm.
[0053] [Table 3]
[0054] <1-5. Formation of vulcanized rubber layer> First, to obtain a core having an adhesive layer for bonding a vulcanized rubber layer, the following procedure was carried out: A conductive vulcanizing adhesive (product name: Metalock U-20; manufactured by Toyo Kagaku Kenkyusho) was applied to the central 222 mm portion in the axial direction of a cylindrical conductive core (steel, nickel-plated surface) having a diameter of 6 mm and a length of 252 mm, and then dried at 80°C for 30 minutes. The conductive rubber composition 1 prepared above was coated on the core metal having the adhesive layer by a crosshead extrusion molding machine to obtain a crown-shaped unvulcanized rubber roller. The molding temperature was 100°C, the screw rotation speed was 10 rpm, and molding was performed while changing the feed speed of the core metal. The die inner diameter of the crosshead extrusion molding machine was 8.4 mm, and the unvulcanized rubber roller was molded to be thick, and the outer diameter of the center in the axial direction of the unvulcanized rubber roller was 8.6 mm, and the outer diameter of the end was 8.5 mm. Thereafter, the layer of the unvulcanized rubber composition 1 was vulcanized by heating at a temperature of 160°C for 60 minutes in an electric furnace to obtain a vulcanized rubber layer. Both ends of the vulcanized rubber layer were cut to obtain a vulcanized rubber roller with an axial length of 232 mm.
[0055] <1-6. Irradiation of vulcanized rubber layer after extrusion with ultraviolet rays> The surface of the obtained vulcanized rubber roller was irradiated with ultraviolet light to obtain a conductive member (charged roller) 1 with a modified conductive layer (surface layer). A low-pressure mercury lamp (product name: GLQ500US / 11, manufactured by Toshiba Lighting & Technology Corporation) was used as the source of ultraviolet light. The charged roller was irradiated with ultraviolet light evenly while rotating. The amount of ultraviolet light was 8000 mJ / cm2 in terms of the sensitivity of a 254 nm sensor. 2 The obtained conductive member 1 was subjected to the following evaluations 1-7 to 1-15.
[0056] <1-7. Confirmation of matrix-domain structure> The presence or absence of a matrix domain structure in the conductive layer was confirmed by the following method. A slice (500 μm thick) was cut out using a razor so that a cross section perpendicular to the longitudinal direction of the conductive layer of the conductive member could be observed. The slices were cut out from 5 equal parts in the longitudinal direction of the conductive layer of the conductive member (conductive roller) and 4 equal parts in the circumferential direction, and one part was cut out from each of the obtained regions, for a total of 20 parts. Next, platinum was vapor-deposited on the surface corresponding to the cross section in the thickness direction of the conductive layer for each slice. The platinum-deposited surface of the slice was photographed at 1000 times magnification using a scanning electron microscope (SEM) (product name: S-4800, manufactured by Hitachi High-Technologies Corporation) to obtain an SEM image. When the conductive layer has a matrix domain structure, it can be confirmed in the SEM image that a plurality of domains are divided by the matrix and that the matrix is connected in the SEM image. Then, it was confirmed that a matrix domain structure exists in the conductive layer for the conductive member 1 according to Example 1 and the conductive members 2 to 19 according to Examples 2 to 19 described later.
[0057] <1-8. Measurement method for volume resistivity of matrix> The volume resistivity of the matrix can be obtained, for example, by cutting out a slice of a predetermined thickness (for example, 1 μm) containing a matrix domain structure from the conductive layer, and contacting the matrix in the slice with a microprobe of a scanning probe microscope (SPM) or an atomic force microscope (AFM) to measure it. Specifically, a slice is cut out from the elastic layer so as to include at least a part of a surface parallel to a YZ plane perpendicular to the axial direction of the conductive member, where the longitudinal direction of the conductive member is the X axis, the thickness direction of the conductive layer is the Z axis, and the circumferential direction is the Y axis. The cutting out can be performed, for example, using a sharp razor, a microtome, or a focused ion beam method (FIB). The volume resistivity is measured by grounding one side of the slice cut out from the conductive layer. Next, a tiny probe of a scanning probe microscope (SPM) or atomic force microscope (AFM) is brought into contact with the matrix on the surface of the flake opposite the ground surface, a DC voltage of 50V is applied for 5 seconds, and the arithmetic average value of the ground current measured for 5 seconds is calculated, and the electrical resistance value is calculated by dividing the applied voltage by this calculated value. Finally, the resistance value is converted to volume resistivity using the film thickness of the flake. At this time, the SPM or AFM can measure the film thickness of the flake at the same time as the resistance value. The value of the volume resistivity R1 of the matrix in a cylindrical electrostatic charging member is determined, for example, by cutting out one thin sample from each of the regions obtained by dividing the conductive layer into four in the circumferential direction and five in the longitudinal direction, obtaining the above-mentioned measured values, and then calculating the arithmetic average value of the volume resistivities of a total of 20 samples. In this embodiment, a thin slice having a thickness of 1 μm was first cut out from the conductive layer of the conductive member using a microtome (trade name: Leica EM FCS, manufactured by Leica Microsystems) at a cutting temperature of −100° C. As described above, the thin slice was cut out so as to include at least a part of the surface parallel to the YZ plane perpendicular to the axial direction (X axis) of the conductive member. In an environment with a temperature of 23° C. and a humidity of 50% RH, one surface of the thin slice (hereinafter also referred to as the “ground surface”) was grounded on a metal plate, and a cantilever of a scanning probe microscope (SPM) (trade name: Q-Scope250, manufactured by Quesant Instrument Corporation) was contacted with a portion of the matrix of the surface of the thin slice opposite to the ground surface (hereinafter also referred to as the “measurement surface”), where no domain exists between the measurement surface and the ground surface. Next, a voltage of 50 V was applied to the cantilever for 5 seconds, and the current value was measured to calculate the arithmetic average value for 5 seconds. The surface shape of the measurement piece was observed with an SPM, and the thickness of the measurement point was calculated from the height profile obtained. Furthermore, the concave area of the cantilever contact point was calculated from the observation of the surface shape. The volume resistivity was calculated from the thickness and the concave area. The conductive layer was divided into 5 equal parts in the longitudinal direction and 4 equal parts in the circumferential direction, and one part was randomly selected from each of the obtained regions, for a total of 20 pieces, and the above measurement was performed on the slices. The average value was taken as the volume resistivity of the matrix. The scanning probe microscope (SPM) (product name: Q-Scope250, manufactured by Quesant Instrument Corporation) was operated in contact mode.
[0058] <1-9. Calculation of volume resistivity of conductive materials> The conductive layer of the charging roller was cut with a razor to obtain a semi-cylindrical rubber slice. The volume resistivity of the cut surface of this rubber was measured by a four-terminal four-probe method. The measurement conditions were a resistivity meter (product name: Loresta GP, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) at 23°C / 50% RH (relative humidity), with an applied voltage of 90V, a load of 10N, a pin-to-pin distance of 1.0mm, a pin tip of 0.04R, and a spring pressure of 250g. The evaluation results of the volume resistivity are shown in Table 7-2.
[0059] <1-10. Measurement of the domain exposure rate in the recess, the recess depth, and the current value by AFM> The surface shape of the charged member, confirmation of the presence of domains at the bottom of the recesses, and the current values of the domains and matrix were measured using an atomic force microscope (AFM) (Easy Scan2, Nanosurf) in the spreading resistance mode. The configuration of the conductivity measuring device is shown in Figure 8. A DC power supply (PL-650-0.1, Matsusada Precision Co., Ltd.) 82 is connected to the conductive substrate of a charging roller 81, a voltage of 80 V is applied, the free end of a cantilever 83 is brought into contact with the conductive layer, and a current image is obtained through the AFM main body 84. In this embodiment, the measurement conditions were as follows: cantilever: ANSCM-PC, operation mode: spreading resistance, measurement environment: in air, set point: 20 nN, P-gain: 3000, I-gain: 600, D-gain: 0, tip voltage: 3 V, image width: 100 μm, number of lines: 256. During this AFM measurement, a topographical image and a current image were simultaneously acquired. The region (121 in FIG. 12) in which the current value is one order of magnitude smaller than the average value in the current image line profile shown in FIG. 12 was extracted as the domain. The number of extracted domains was counted and used as the total number of domains exposed on the outer surface. Then, the number of exposed domains that were concave with respect to the outer surface was counted from the line profile of the AFM shape image shown in Figure 9. As mentioned above, the exposed domain was defined as being concave when the average value of the height direction Z of the domain was 1.0 μm or more lower than the average value of the height direction Z of the domain other than the domain. The value obtained by dividing the number of domains that were concave with respect to the outer surface by the total number of domains on the outer surface mentioned above was used as the domain exposure rate at the concave portion. The results are shown in Table 7. The depth of the recess was determined by subtracting the average value of the height direction Z of the domain from the average value of the height direction Z of the other than the domain. The depth of the recess is shown in Table 7. In addition, the average current value of the domain extracted when calculating the depth of the recess was taken as A2. On the other hand, the area other than the domain was taken as the matrix, and the average current value of the matrix was taken as A1. The larger A2 / A1 indicates that the electrical resistance of the domain is lower than that of the matrix. The results of A2 / A1 are shown in Table 7-2.
[0060] <1-11. Domain diameter D> In the measurement of the domain diameter D according to the present disclosure, the cross-sectional area S of the domains existing within a 15 μm square region was calculated using a counting function on the binary image obtained in the measurement for confirming the matrix-domain structure described above [1-7]. The circle equivalent diameter was calculated from the domain area S. Specifically, the domain area S was used to calculate D=(4S / π) 0.5 was calculated. In the measurement of the domain diameter D, the conductive layer of the conductive member was divided into 4 in the circumferential direction and 5 in the longitudinal direction. In any part of each of these regions, a thin sample was cut out from each region and measured in the same manner as in the measurement method of the domain shape described above. Measurements were performed in a total of 16 regions divided into 4 in the longitudinal direction and 4 in the circumferential direction, and the average value was calculated to obtain the domain diameter D. The results are shown in Table 7-2.
[0061] <1-12. Domain distance> The interdomain distance was measured by observing an image obtained by measuring the domain diameter and processing the observed image. Specifically, for the above-mentioned domain size measurement method, an image processing software (product name: LUZEX, manufactured by Nireco Corporation) was used to calculate the arithmetic mean value from the distribution of the distance between the wall surfaces of the domains. Measurements were performed in a total of 16 regions divided into 4 in the longitudinal direction and 4 in the circumferential direction, and the mean value was calculated to be the domain distance. The evaluation results are shown in Table 7-2.
[0062] <1-13. Measurement of discharge width at upstream of nip> The discharge width was measured by directly observing the discharge light behind a dark curtain as follows. First, a photosensitive drum imitation glass 102 (width 250 mm, length 300 mm, thickness 5 mm) was prepared to simulate a photosensitive drum, as shown in Fig. 10. A jig was made so that the charging roller 101 could be brought into contact with it, and the photosensitive drum imitation glass 102 was moved in the contact state to drive the charging roller 101, thereby reproducing the rotation inside the process cartridge. Generally, the discharge width and discharge start distance are several hundreds of μm, while the outer diameter of the photosensitive drum is as large as 20 to 30 mm, so it can be substituted by measurement using the flat photosensitive drum simulating glass as described above. The photosensitive drum imitation glass was provided with a transparent conductive film and a transparent resin film so that a voltage could be applied between it and the charging roller to generate a discharge. The transparent conductive film was made by coating ITO (indium tin oxide) on the glass only on the surface that the charging roller contacted, using a method such as sputtering. The electrical resistance of the transparent conductive film was 200 Ω when measured on the surface with a two-terminal tester. Next, polyethylene terephthalate with a volume resistivity equivalent to that of the photosensitive drum surface layer was dissolved in an organic solvent such as chlorobenzene, and the solution was dipped and dried with hot air. death, A transparent resin film was formed on the transparent conductive film. The transparent resin film had a thickness of 20 μm. First, the center of the contact part with the glass was observed under a bright light environment using a high-speed camera (FASTCAM SA5, manufactured by Photron) 104 and an image intensifier (C9547-2, manufactured by Hamamatsu Photonics) 106. During the observation, the angle of view of the high-speed camera was 1024 pixels x 1024 pixels, the frame rate was 500 fps, and the gain of the image intensifier was 800. At this time, the contact area of the observed image is band-shaped as shown in FIG. 11B, and the load for pressing the charging roller against the photosensitive drum simulation glass was adjusted so that the contact width Y was 500 μm. The contact width was calculated by measuring the corresponding number of pixels and converting it from the observation magnification. Thereafter, the discharge width was measured with the device surrounded by a blackout curtain 103. Using the high-speed camera (FASTCAM SA5, manufactured by Photron) 104 and image intensifier 106, the discharge light generated in the gap with the charging roller 101 was observed through the photosensitive drum simulation glass 102. During the observation, the angle of view of the high-speed camera was 1024 pixels x 1024 pixels, the frame rate was 500 to 4000 fps, and the gain of the image intensifier was 700 to 900. The photosensitive drum simulation glass was grounded, and a DC voltage of -1300 V was applied to the charging roller 101 using a high-voltage power supply (Trek615-3, manufactured by Trek Japan) 105 connected to the charging roller. After the DC voltage was applied, the photosensitive drum simulation glass 102 started to move at a speed of 200 mm / sec, and one second later, photography was started and continued for two seconds. Discharge occurring in the gap between the charging roller 101 and the dark curtain 103 was observed. The discharge light image observed is shown in FIG. 11A A. Since the image is observed through the photosensitive drum simulation glass 102, a strip-shaped image is observed. Image (discharge area 112) In FIG. 11B, the discharge region 111 is 112 , photosensitive drum imitation glass 102 and charging roller 101 The contact area 116 and the photosensitive drum simulation Glass 102 As shown in FIG. 11A, the discharge region 112 is generated on the upstream side (on the paper surface) with respect to the traveling direction of the photosensitive drum simulation glass 102. The discharge light image is processed by image processing software (product name: "ImageProPlus」; The number of pixels corresponding to the discharge width X was measured using a microscope manufactured by Media Cybernetics, and the number was converted into a discharge distance of 114 based on the observation magnification. In the case of a cylindrical charging roller, the conductive layer of the charging member was divided into four in the longitudinal direction and four in the circumferential direction, resulting in a total of 16 regions, and measurements were taken at arbitrary locations in each region, and the arithmetic average value of the total of 16 regions was calculated as the discharge width. The evaluation results are shown in Table 7-2.
[0063] <1-14. Measurement of horizontal distance at which discharge begins upstream of the nip> The discharge start horizontal distance was calculated by the following procedure. The discharge most upstream position 113 was calculated from the observation image of the discharge light (A in FIG. 11A). Next, the center position 115 of the contact area was calculated from the contact image (B in FIG. 11B) between the charging roller and the photosensitive drum simulation glass. The center position of the contact area was calculated as (Y1+Y2) / 2 using the image height coordinate Y1 of the discharge most upstream position 113 and the image height coordinate Y2 of the discharge most downstream position in the observation image 11(a). As in the measurement of the discharge width X, the number of pixels of the distance 114 between the center position 115 of the contact area in FIG. 11B and the above-mentioned discharge most upstream position 113 was measured using image processing software (product name: ImageProPlusMedia, Cybernetics). The observation magnification was converted into the discharge start horizontal distance L. In the case of a cylindrical charging roller, the conductive layer of the charging member was divided into four in the longitudinal direction and four in the circumferential direction, resulting in a total of 16 regions, and measurements were taken at arbitrary locations in each region, and the arithmetic average value of the total of 16 regions was calculated as the horizontal discharge start distance. The evaluation results are shown in Table 7-2.
[0064] <1-15. Image evaluation> First, an electrophotographic laser printer (product name: LBP352i, manufactured by Canon) was prepared as an electrophotographic image forming apparatus, which was modified so that a high voltage could be applied to the charging member and the developing member from an external power source (product name: Model 615, manufactured by Trek Japan Co., Ltd.) Next, the charging roller 1, the electrophotographic image forming apparatus, and the process cartridge were left in an environment of 23°C / 50% RH for 24 hours in order to acclimate them to the measurement environment. In order to evaluate in a high-speed process, the laser printer was modified so that the number of sheets output per unit time was 75 sheets per minute on A4-sized paper, which is more than the original number of output sheets. At that time, the output speed of the recording medium was 370 mm / second and the image resolution was 1,200 dpi. Then, a DC voltage of -1000 V was applied to the conductive support of the conductive member. The upper 10 cm of the image was an image in which the letter "E" of the alphabet with a size of 4 points was printed so that the coverage rate was 4% with respect to the area of the A4-sized paper. As a result, after the transfer process, that is, unevenness along the surface potential corresponding to the first letter "E" can be formed in the region of about one circumference of the photosensitive drum on the surface potential of the photosensitive drum before the charging process. Furthermore, in the lower part than 10 cm, a halftone (an image in which horizontal lines with a width of 1 dot and an interval of 2 dots are drawn in a direction perpendicular to the rotation direction of the photosensitive drum) image was output. Whether or not the letter "E" before one circumference of the photosensitive drum appeared on this halftone image was evaluated according to the following criteria. The evaluation results are shown in Table 7-2.
[0065] [Evaluation of the letter "E" on the halftone image] Rank A: Even when observed with a microscope, no image unevenness derived from the letter "E" is visible on the halftone image. Rank B: Visually, there is no image unevenness derived from the letter "E" in a part of the halftone image, but when observed with a microscope, image unevenness derived from the letter "E" is observed. Rank C: The image of the letter "E" is visible in a part of the halftone image visually. Rank D: The image of the letter "E" is visible over the entire halftone image visually.
[0066] [Preparation of CMB2 to CMB8] CMB2 to CMB8 were prepared in the same manner as CMB1, except that the materials described in Table 4 were used in the blending amounts shown in Table 4. Also, the die well value was calculated in the same manner as CMB1.
[0067]
Table 4
[0068] In Table 4, as the conductive particles / conductive agent, each grade of "Tokablack" manufactured by Tokai Carbon Co., Ltd. represents carbon black particles, and "SN100-P" manufactured by Ishihara Sangyo Co., Ltd. represents Sb-doped SnO2 particles. "ADEKA Sizer LV70" manufactured by ADEKA Corporation is an antistatic agent (quaternary ammonium salt).
[0069] <Preparation of MRC2 to MRC9> MRC2 to MRC9 were prepared in the same manner as MRC1, except that the materials described in Table 5 were used in the compounding amounts shown in Table 5. Also, the die swell value was calculated in the same manner as MRC1.
[0070]
Table 5
[0071] <Preparation of Conductive Rubber Compositions 2 to 18 and 20> Conductive rubber compositions 2 to 18 and 20 were prepared in the same manner as conductive rubber composition 1, except that the starting materials shown in Table 6 were used. Table 6 shows the parts by mass and physical properties of the starting materials used in the production of each conductive member.
[0072]
Table 6
[0073] 〔Examples 2 to 19〕 <Conductive Members 2 to 19> Conductive members 2 to 19 were prepared in the same manner as conductive member 1, except that the starting materials shown in Table 6 were used. Table 7-1 shows the conductive rubber compositions (MRC, CMB, domain ratio) used in the production of each conductive member, the die swell ratio during extrusion molding, and Table 7-2 shows various physical properties and image evaluation results. The domain ratio is the mass ratio [CMB / (MRC + CMB)] of the rubber composition for domain formation to the total rubber composition, expressed as a percentage.
[0074] [Table 7-1]
[0075] [Table 7-2]
[0076] Comparative Example <Comparative Example 1> <Preparation of Conductive Member 20> A conductive member 20 was produced in the same manner as in Example 2, except that the conductive rubber composition 2 was used, the outer diameter during extrusion was changed to 9.0 mm at the center, and an additional polishing step was performed after extrusion. The polishing process was carried out under the following conditions. An elastic roller with an outer diameter of 9.0 mm was molded to 8.5 mm and a crown amount of 100 μm. The conditions for the polishing process were a grindstone rotation speed of 2100 rpm and an elastic roller rotation speed of 250 rpm. In the rough cutting process, the grindstone was inserted into the elastic roller at a penetration speed of 20 mm / sec, and was inserted 0.24 mm after contacting the outer peripheral surface of the elastic roller. In the fine polishing process, the penetration speed was changed to 0.2 mm / sec, and after inserting 0.01 mm, the grindstone was applied at that position for 4 seconds, and then the grindstone was removed from the roller. In addition, an upper cut method was used in which the rotation direction of the polishing grindstone and the rubber roller was the same. A porous grindstone made of GC80 (manufactured by Teiken) abrasive grains with a width of 235 mm and a diameter of Φ305 mm was used as the grindstone. Details regarding the manufacture of the conductive member 20 are shown in Table 11-1, and various physical properties and image evaluation results are shown in Table 11-2. When I did an image evaluation, it was ranked D. This is because Most Since the exposed domains on the surface were not recessed, the discharge width could not be expanded toward the side near the nip, and the potential leveling effect was insufficient.
[0077] <Comparative Example 2> <Preparation of Conductive Rubber Composition 19> The compounding agent 1 in Table 8 below was mixed under the following conditions. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes. Thereafter, the obtained rubber composition and compounding ingredient 2 shown in Table 8 were mixed with an open roll to prepare conductive rubber composition 19. An open roll with a roll diameter of 12 inches was used as the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.5 mm.
[0078] [Table 8]
[0079] <Preparation of Conductive Member 21> Except for using the conductive rubber composition 19, the conductive member 21 was produced in the same manner as the conductive member 1. Details regarding the production of the conductive member 21 are shown in Table 11-1, and various physical properties and image evaluation results are shown in Table 11-2. The image of the conductive member 21 was evaluated and given a rank of D. The conductive member 21 does not have a matrix-domain structure, and the domain is not located in a recess, so the discharge width cannot be expanded by micro-discharge, and the potential leveling effect is insufficient.
[0080] <Comparative Example 3> <Preparation of Conductive Member 22> Except for using the conductive rubber composition 20, the conductive member 22 was produced in the same manner as the conductive member 1. Details regarding the production of the conductive member 22 are shown in Table 11-1, and various physical properties and image evaluation results are shown in Table 11-2. The image evaluation of the conductive member 22 gave it a rank of D. This is because the MRC / CMB of the conductive rubber composition is 1.00, and the conductive member 22 is Most The exposed domains on the surface were not concave, which meant that the discharge width was not expanded and the potential was not evened out sufficiently.
[0081] <Comparative Example 4> <Preparation of Conductive Rubber Composition 21> The compounding agent 1 in Table 9 was mixed under the following conditions. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes. Thereafter, the obtained rubber composition and compounding ingredient 2 shown in Table 9 were mixed with an open roll to prepare conductive rubber composition 21. An open roll with a roll diameter of 12 inches was used as the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.5 mm.
[0082] [Table 9]
[0083] <Conductive member 23> A conductive member 23 was produced in the same manner as in Example 2, except that the conductive rubber composition 21 was used, the outer diameter during extrusion was changed to 9.0 mm at the center, and an additional polishing step was performed after extrusion. The polishing process was carried out under the following conditions. An elastic roller with an outer diameter of 9.0 mm was molded to 8.5 mm and a crown amount of 100 μm. The conditions for the polishing process were a grindstone rotation speed of 2100 rpm and an elastic roller rotation speed of 250 rpm. In the rough cutting process, the grindstone was intruded into the elastic roller at a penetration speed of 20 mm / sec, and was allowed to penetrate 0.24 mm after contacting the outer circumferential surface of the elastic roller. In the fine polishing process, the penetration speed was changed to 0.2 mm / sec, and after intrusion of 0.01 mm, the grindstone was removed from the elastic roller to complete the polishing process. In addition, an upper cut method was used in which the rotation direction of the polishing grindstone and the rubber roller was the same. A porous grindstone made of GC80 (manufactured by Teiken) abrasive grains with a width of 235 mm and a diameter of Φ305 mm was used as the grindstone. Details regarding the manufacture of the conductive member 23 are shown in Table 11-1, and various physical properties and image evaluation results are shown in Table 11-2. The image was evaluated as rank D. This is because the conductive member 23 has a conductive convex portion derived from the spherical carbon particles, which expands the discharge width, but the discharge width is not large toward the upstream side of the nip. Release of Since the horizontal distance at which the discharge started was large and the discharge spread toward the upstream side of the nip rather than the vicinity of the nip, abnormal discharge occurred and the effect of leveling the potential by micro-discharges was insufficient.
[0084] <Comparative Example 5> <Preparation of Conductive Rubber Composition 22> The compounding agent 1 in Table 10 below was mixed under the following conditions. A 6-liter pressure kneader (product name: TD6-15MDX, manufactured by Toshin Co., Ltd.) was used as the mixer. The mixing conditions were a filling rate of 70 vol%, a blade rotation speed of 30 rpm, and 16 minutes. Thereafter, the obtained rubber composition and compounding ingredient 2 shown in Table 10 were mixed with an open roll to prepare conductive rubber composition 22. An open roll with a roll diameter of 12 inches was used as the mixer. The mixing conditions were a front roll rotation speed of 10 rpm, a rear roll rotation speed of 8 rpm, a roll gap of 2 mm, and a total of 20 left and right turns, followed by 10 thin passes with a roll gap of 0.5 mm.
[0085] [Table 10]
[0086] <Conductive member 24> Except for the case where the conductive rubber composition 22 was used, the elastic layer was prepared in the same manner as the conductive member 1. , to obtain an elastic roller A surface layer was formed by the following method, and a conductive member 24 was produced. As the first resin, nylon resin (N-methoxymethylated nylon, product name: FR101, manufactured by Lead City Co., Ltd.) was dissolved in a mixture of methanol and 1-butanol (methanol: 1-butanol = 3: 1 (mass ratio)) and adjusted to a solid content concentration of 8 mass%. 10 parts by mass of polystyrene (product name: styrene monomer, manufactured by Sunlight Co., Ltd.) as the second resin, 12 parts by mass of carbon black (product name: MONARCH880, manufactured by Cabot Co., Ltd.), and 2 parts by mass of a curing agent (citric acid) were added to 100 parts by mass of the above solution, and the mixture was dispersed in a bead mill and diluted with methanol to obtain a dispersion. The above elastic roller was immersed in the dispersion and coated, and then heated and dried at 160 ° C for 20 minutes to form a surface layer. Details regarding the manufacture of the conductive member 24 are shown in Table 11-1, and various physical properties and image evaluation results are shown in Table 11-2. The image was evaluated and ranked as D. The conductive member 24 had a matrix-domain structure in the surface layer, and the conductive agent was unevenly distributed in the domain portion. Most Because the exposed domains on the surface were not recessed, the discharge width could not be expanded toward the nip, and because the elastic layer did not form a matrix-domain structure, the potential leveling effect of the micro-discharges was insufficient.
[0087] [Table 11-1]
[0088] [Table 11-2] [Explanation of symbols]
[0089] 11 Conductive materials 12 Conductive support 13 Conductive layer 21. Matrix 22 Domain 31 Most surface 32 Domains exposed in recesses 50 Extrusion Machine 51 Core 52 Unvulcanized rubber composition 53 Unvulcanized rubber roller 54 Crosshead 55 Transport roller 56 Cylinder 57 Screw 58 Dice 61 Photoreceptor 62 Charging roller 63 power supply 64 Exposure light 65 Developing roller 66 Transfer roller 67 Fixing member 68 Cleaning materials 69 Collection container 71 Photoreceptor 72 Developing roller 73 Cleaning materials 74 Charging roller 81 Charging roller 82 DC power supply 83 Cantilever 84 AFM main unit 91 Domains exposed in recesses 101 Charging roller 102 Photosensitive drum simulation Glass 103 Blackout Curtain 104 High Speed Camera 105 High voltage power supply 106 Image Intensifier 111 Charging materials 112 discharge area 113 Discharge most upstream position 114 Discharge start horizontal distance 115 Abutment Area center position 116 contact area
Claims
1. A conductive member having a conductive support and a conductive layer, the conductive layer is a surface layer of the conductive member constituted by a single layer, the conductive layer has a matrix containing a crosslinked product of a first rubber and a plurality of domains dispersed in the matrix, Each of the domains includes a crosslinked product of a second rubber and conductive particles, the outer surface of the conductive member has a plurality of recesses; At least a portion of the surface of the domain is exposed to the outer surface of the conductive member at the bottom of the recess; The volume resistivity of the matrix is 1.0×10 12 Larger than Ωcm, The volume resistivity of the conductive layer is 1.0×10 5 Ωcm or more 1.0×10 8 Ωcm or less, A current value when a direct current voltage of 80 V is applied between the conductive support and a cantilever of an atomic force microscope brought into contact with the surface of the matrix constituting the outer surface of the conductive member is defined as A1; A conductive member characterized in that, when a direct current voltage of 80 V is applied between the conductive support and a cantilever of an atomic force microscope brought into contact with the surface of the domain constituting the outer surface of the conductive member, A2 is equal to or greater than 20 times A1.
2. 2. The conductive member according to claim 1, wherein the ratio of domains present on the outer surface that are exposed on the outer surface of the conductive member at the bottoms of the recesses is 50% or more.
3. 3. The conductive member according to claim 1, wherein the first rubber is a styrene-butadiene rubber.
4. 4. An electrophotographic image forming apparatus comprising an electrophotographic photoreceptor and a charging member arranged so as to be capable of charging the electrophotographic photoreceptor, wherein the charging member is the conductive member according to any one of claims 1 to 3.
5. A process cartridge that is detachably mountable to a main body of an electrophotographic image forming apparatus, 4. A process cartridge comprising: an electrophotographic photosensitive member; and a charging member arranged so as to be capable of charging the electrophotographic photosensitive member, the charging member being the conductive member according to claim 1.
6. A method for producing a conductive member according to any one of claims 1 to 3, comprising the steps of: The following steps (A) to (D): (A) preparing a domain-forming rubber composition comprising the conductive particles and the second rubber; (B) preparing a rubber composition for forming a matrix containing the first rubber; (C) kneading the domain-forming rubber composition with the matrix-forming rubber composition to prepare a rubber composition having a matrix-domain structure; and (D) extruding the rubber composition having a matrix-domain structure from a crosshead together with a conductive support to cover the periphery of the conductive support with the rubber composition having a matrix-domain structure; Have The method for producing a conductive member is characterized in that, when a die swell value of the rubber composition for forming a domain is DS(d) and a die swell value of the rubber composition for forming a matrix is DS(m), the ratio of the die swell values, DS(m) / DS(d), is greater than 1.
00.
7. The method for producing a conductive member according to claim 6, wherein the DS(m) / DS(d) is 1.15 or more.
8. The volume resistivity of the conductive layer is 1.0×10 5 Ωcm or more 1.0×10 8 Ωcm or less, A current value when a DC voltage of 80 V is applied between the conductive support and a cantilever of an atomic force microscope brought into contact with the surface of the matrix constituting the outer surface of the conductive member is defined as A1; 8. The method for producing a conductive member according to claim 6 or 7, wherein when a direct current voltage of 80 V is applied between the conductive support and a cantilever of an atomic force microscope brought into contact with the surface of the domain constituting the outer surface of the conductive member, A2 is equal to or greater than 20 times A1, where A2 is a current value when A2 is a current value when A2 is applied between the conductive support and a cantilever of an atomic force microscope brought into contact with the surface of the domain constituting the outer surface of the conductive member, A2 is equal to or greater than A1.
Citation Information
Patent Citations
Conductive roll
JP1990018578A
Developing device
JP1993072889A
Semiconductive rubber composition, electrified member, electrophotographic device and process cartridge
JP2002003651A
Charging member, process cartridge, and electrophotographic image forming apparatus
JP2018063423A
Electrophotographic charging member, process cartridge and electrophotographic image forming apparatus
JP2019124900A